Respuesta :

The equation that expresses the solution to the quadratic equation x² - 10x + 13 = 0 is [tex]x =5 \pm 2\sqrt{3}[/tex]

How to express the solution?

The equation is given as:

x² - 10x + 13 = 0

The solution to a quadratic equation is represented by:

[tex]x =\frac{-b \pm \sqrt{b^2 -4ac}}{2a}[/tex]

So, we have:

[tex]x =\frac{10 \pm \sqrt{(-10)^2 -4 * 1 * 13}}{2 * 1}[/tex]

Evaluate the radicand

[tex]x =\frac{10 \pm \sqrt{48}}{2}[/tex]

Take the square root of 48

[tex]x =\frac{10 \pm 4\sqrt{3}}{2}[/tex]

Divide

[tex]x =5 \pm 2\sqrt{3}[/tex]

Hence, the equation that expresses the solution to the quadratic equation x² - 10x + 13 = 0 is [tex]x =5 \pm 2\sqrt{3}[/tex]

Read more about quadratic equations at:

https://brainly.com/question/8649555

#SPJ1